2012
DOI: 10.1515/1548-923x.2239
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of the Norwegian Version of the Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T) Evaluation Scale

Abstract: Several instruments have been developed to monitor nursing students' subjective evaluation of clinical placement. The Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T) evaluation scale measures five dimensions. The purpose of this study was to translate and test the construct validity and internal consistency of the evaluation scale within a Norwegian context. The questionnaire was distributed to all students in four university colleges (n=1229) in 2009 with a response rate of 41.6 % (n=511… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
7
27
0
2
Order By: Relevance
“…In the present study, the "supervisory relationship" was identified as the most significant factor in the clinical learning environment, consistent with similar results obtained in previous research on this instrument (Bergjan and Hertel, 2013;Henriksen et al, 2012;Johansson et al, 2010;Papastavrou et al, 2010;Saarikoski et al, 2008). "Pedagogical atmosphere on the ward" was the second most important factor, in agreement with the findings reported by Bergjan and Hertel (2013), Henriksen et al (2012), Johansson et al (2010) and Saarikoski et al (2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the "supervisory relationship" was identified as the most significant factor in the clinical learning environment, consistent with similar results obtained in previous research on this instrument (Bergjan and Hertel, 2013;Henriksen et al, 2012;Johansson et al, 2010;Papastavrou et al, 2010;Saarikoski et al, 2008). "Pedagogical atmosphere on the ward" was the second most important factor, in agreement with the findings reported by Bergjan and Hertel (2013), Henriksen et al (2012), Johansson et al (2010) and Saarikoski et al (2008).…”
Section: Discussionsupporting
confidence: 92%
“…"Pedagogical atmosphere on the ward" was the second most important factor, in agreement with the findings reported by Bergjan and Hertel (2013), Henriksen et al (2012), Johansson et al (2010) and Saarikoski et al (2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2.4.2. Students' satisfaction with clinical placement tool was developed by the researchers, based on reviewing literature and instruments related to the study scope [9], [31], and [32]. It is a self-report Arabic questionnaire designed to measure the nursing students' satisfaction with the clinical placement.…”
Section: Data Collection Toolsmentioning
confidence: 99%